Airway management in patients with COVID-19: an updated guide for clinicians in the emergency department. Issue 4 (16th October 2022) - Erenler, Ali Kemal; Komut, Seval; Çapraz, Mustafa; Baydin, Ahmet
Abstract : The coronavirus disease, also known as Coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome-coronavirus-2 virus has changed the characteristics of many methods used by healthcare providers. These modifications aimed to provide safety and reduce the risk of virus transmission. Some of the recommendations to reduce the risk of aerosol transmission during the intubation are usage of personal protective equipment (PPE) and video laryngoscopy (VL). After satisfactory preoxygenation, along with sedation and paralysis of the patient, modified rapid sequence induction is the recommended technique. Intubation timing and period should be arranged well in order to minimize aerosol spread. During intubation, barrier devices, such as screens and intubation boxes should be considered. Patient coughing during intubation can generate aerosols and should be avoided. Gentle airway manipulation is assured. It is prudent to use VL rather than direct laryngoscopy for intubation because VL increases the distance between the healthcare worker's face and the patient's face, which may minimize the risk of contamination. In this narrative review, we aimed to focus on protective measures and modifications occurred during COVID-19 pandemic.